Civil Service: leadership, transformation and succession Plan - Mahbob, Sulaiman; Abdul Rahman, Abdullah; Nik Mahmod, Nik Ahmad Kamal (Malaysian Industry-Governmemnt Group for Hgh Technology, 2014)
an interview session with three prominent figures in civil service to explore a top down approach on future of public service